Effect of Dynamic Corrosion and Degradation on Fatigue Life of an AA2024-T3 Aircraft Profile: Experimental, Statistical, and Numerical Analyses - Gilberto Daniel Conejo Magaña; Víctor García García; Daniel Cahue Díaz; Nicolás Herrera-Sandoval; Orlando Hernández Cristóbal (Crystals)
The effect of parameters such as angle of attack, flow velocity, and electrolyte concentration (saline solution) on the extent of material degradation, as well as the morphology and depth of corrosion pits in an airfoil made of 2024-T3 aluminum alloy, was studied in detail. An orthogonal L9 design of experiments (Taguchi method) was applied to promote high pitting corrosion through the quality characteristic “the higher the better”. Potentiodynamic curves of the three experiments with low, medium, and high saline concentration were obtained through the CorrTest CS350 equipment. The above allowed the determination of the electrochemical corrosion parameters under static test conditions. The corroded airfoils were analyzed using light optical microscopy (LOM). In addition, the roughness measurements correlated with the extent of the degraded surface. A complete pit shape and depth characterization was obtained by applying mechanical ground, surface wear level monitoring (every 0.01 mm), and LOM observations. Pitting defects (depth and morphology) and mechanical strength reduction were considered by a finite element (FE) model to simulate the airfoil fatigue behavior. Numerical results helped to determine the contribution of pitting and the extent of degradation on sudden airfoil failure.